An index of treasury market liquidity: 1991-2017 - Tobias Adrian; Michael Fleming; Erik Vogt (Federal Reserve Bank of New York, 2017)
Order book and transactions data from the U.S. Treasury securities market are used to calculate daily measures of bid-ask spreads, depth, and price impact for a twenty-six-year sample period (1991-2017). From these measures, a daily index of Treasury market liquidity is constructed, reflecting the fact that the varying measures capture different aspects of market liquidity. The liquidity index is then correlated with various metrics of funding liquidity, volatility, and macroeconomic conditions. The liquidity index points to poor liquidity during the 2007-09 financial crisis and around the near failure of Long-Term Capital Management, but suggests that current liquidity is good by historical standards. Market liquidity tends to be strongly correlated with funding liquidity at times of market stress, but otherwise exhibits little correlation.
Keywords: G12; 330; Treasury securities; market liquidity; funding liquidity; volatility; index